Advertising Slogans in Translation: A Functionalist Approach Corpus-Based Study - Górski, Tomasz P. (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
The aim of the paper is an attempt to present and to analyse advertising slogans from the point of view of functionalist approach as developed by its leading propagator Christiane Nord, though the ideas of Katharina Reiss and Hans Vermeer are also important points of reference. It discusses 75 advertising slogans, sets them against the background of product localisation, focuses on cultural, ethical, linguistic and formal issues of the slogans to finally sort them according to the methods of translation developed by Peter Newmark, namely transference, literal translation, and non-literal translation (adaptation). The English language version of the slogan is contrasted here with the Polish one and, in a few cases, with French and German. A qualitative analysis of the material shows the slogan translators’ consistency with the assumptions of functional approach and cultural specificity of the target receivers.
Keywords: advertisement; advertising slogan; functional approach; translation methods